A raven's battle-cry the limits of judgment in the medieval Irish legal tract Anfuigell - Eska, Charlene M. (Brill, 2019)
Charlene M. Eska presents a critical edition and translation of the previously unpublished medieval Irish legal tract 'Anfuigell'. Although the Old Irish text itself is fragmentary, the copious accompanying commentaries provide a wealth of legal, historical, and linguistic information not found elsewhere in the medieval Irish legal corpus. 'Anfuigell' contains a wide range of topics relating to the role of the judge in deciding difficult cases, including kingship, raiding, poets, shipwreck, marriage, fosterage, divorce, and contracts relating to land and livestock
Keywords: Geschichte 500-1500; Recht; Irland; Anfuigell; Law / Ireland / History / To 1500 / Manuscripts; Irish language / To 1100 / Texts; Irish language; Law / Manuscripts; Ireland; To 1500; History; Texts; Quelle